2020
DOI: 10.2172/1677477
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Wind Technology Data Update (2019) [Slides]

Abstract: s (NREL's) internal offshore wind database, which is built on internal research and a wide variety of data sources, including peer-reviewed literature, press releases, industry news reports, manufacturer specification sheets, and global offshore wind project announcements. For the database, NREL has verified and sourced data from the following publications:• The 4C Offshore Wind Database (4C Offshore 2020) • Bloomberg New Energy Finance (BNEF) Renewable Energy Project Database (BNEF 2020) • 4C Offshore Vessel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…Figure 8 shows the average LCOE as a function of the flexibility range. The average LCOE values vary between 65 and 95 €/M W h, which is similar to the values described in the most recent technical reports [43,44]. It can be observed that the lowest LCOE is produced by the unchangeable system (case (iv)) followed by Strategy B and the baseline case.…”
Section: Size Of Flexibility Spacesupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 8 shows the average LCOE as a function of the flexibility range. The average LCOE values vary between 65 and 95 €/M W h, which is similar to the values described in the most recent technical reports [43,44]. It can be observed that the lowest LCOE is produced by the unchangeable system (case (iv)) followed by Strategy B and the baseline case.…”
Section: Size Of Flexibility Spacesupporting
confidence: 85%
“…Again, the parameters of the variables used in the example are summarized in Table 11. Function cf (t) represent a rapidly oscillating tendency between typical values reported in the literature [42,43,44]. The increment in the uncertainty over time is a modeling decision that attempts to capture the difficulty of predicting for such long time periods.…”
mentioning
confidence: 99%
“…Historical trends in the cost of wind energy have been driven by changes in the main components of LCOE: energy production, capital costs, operating costs, cost of financing, and lifetime (Blanco, 2009; Short et al, 1995) (Sidebar 2). Several research entities and consultancies collect historical data on LCOE components, such as CapEx, OpEx, capacity factor, cost of financing, and project lifetimes for various countries (IEA Wind Task 26, 2020; Wiser, Bolinger, et al, 2020, Musial et al, 2020; Wood MacKenzie, 2019; IRENA, 2020; Lazard, 2020; BNEF, 2020; Vieira et al, 2019; Ioannou et al, 2018; Kost et al, 2018; Durstewitz et al, 2017; Wallasch et al, 2019; Wiser & Bolinger, 2019c; Wiser et al, 2019; Hamilton et al, 2020; Staffell & Green, 2014). Energy production is influenced by the site‐specific wind resource as well as technical design choices such as specific power 4 .…”
Section: Quantitative Trends In the Historical Cost Of Wind Energymentioning
confidence: 99%
“…The global average LCOE for offshore wind in 2019 was $115/MWh, more than twice the 2019 LCOE for onshore wind (IRENA, 2020). To date, worldwide floating offshore wind installations are limited to 13 projects, representing 84 MW of capacity (Musial et al, 2020). Estimated LCOE for commercial‐scale floating projects in 2019 ranged between $95/MWh and $175/MWh, with significant reductions expected as the industry develops (Beiter et al, 2020; Musial et al, 2020).…”
Section: Quantitative Trends In the Historical Cost Of Wind Energymentioning
confidence: 99%
See 1 more Smart Citation